Studi Kasus Strategi Coping Stres Pada Ibu Rumah Tangga dengan Kecenderungan Psikosomatis di Yogyakarta - Widuri Mayangsari; Arundati Shinta; FX. Wahyu Widiantoro (Jurnal Psikologi, 2022)
This research was conducted to determine the coping efforts of a person who has psychosomatic tendencies in dealing with stress. Data were collected by means of interviews about the background, psychosomatic causes, then coping strategies that were used to control oneself when these symptoms came. This study used a qualitative approach with a case study method which was conducted on two research subjects. The subjects of this study were housewives who had psychosomatic tendencies when dealing with stressors. The results showed that a person with psychosomatic tendencies tends to do Emotional-focused coping, including efforts to treat illness, efforts to get closer to God and efforts to control his emotions. Problem-focused coping includes a willingness to go to a doctor if symptoms recur and an effort to seek support from people around them as a coping strategy.